Tribological behaviour of AISI 1045 carbon steel in metalworking fluid containing Pseudomonas pseudoalcaligenes. (18th February 2022) - Li, Qinghong; Dong, Yaohua; Han, Mingmou; Zhu, Hongling; Shen, Yuanyuan; Zhang, Li; Dong, Lihua; Chen, Jinghao
Abstract: The microbial contamination of metalworking fluid (MWF) has been increasingly recognised as an issue in the machining industry. To investigate the effects of microbes on the tribological behaviour of AISI 1045 carbon steel in the MWF, a strain of Pseudomonas pseudoalcaligenes was isolated from waste metalworking fluid (WMWF). The biodegradation of MWF and the tribological behaviour of carbon steel in MWF in the presence of bacteria and its extracellular polymeric substances (EPS) were studied. The results showed that the buffer agent and emulsifier were severely biodegraded. The lubricity of the MWF increased first and then dramatically decreased, resulting in a similar trend for the wear of carbon steel in MWF upon prolonging the culture time. The wear mechanism of carbon steel involved a transformation from abrasive wear into tribo‐corrosion wear. Remarkably, the lubricity of the MWF was enhanced during the exponential microbial growth stage due to the synergistic reduction in friction by the layer of adsorbed EPS and the additive layer.